2005
DOI: 10.1038/sj.bjc.6602623
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors and delays in the diagnosis of six cancers: analysis of data from the ‘National Survey of NHS Patients: Cancer’

Abstract: This paper aims to explore the relationship between sociodemographic factors and the components of diagnostic delay (total, patient and primary care, referral, secondary care) for these six cancers (breast, colorectal, lung, ovarian, prostate, or non-Hodgkin's lymphoma). Secondary analysis of patient-reported data from the 'National Survey of NHS patients: Cancer' was undertaken (65 192 patients). Data were analysed using univariate analysis and Generalised Linear Modelling. With regard to total delay, the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
171
7
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(199 citation statements)
references
References 9 publications
19
171
7
2
Order By: Relevance
“…Data regarding the use of health services among people with cancer from different ethnic groups are limited. A study of the relationship between socio-demographic factors and the components of diagnostic delay (total, patient and primary care, referral and secondary care) for six cancers (breast, colorectal, lung, ovarian, prostate and non-Hodgkin's lymphoma) found that there was greater diagnostic delay for breast cancer for black and South Asian groups (Neal and Allgar, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the use of health services among people with cancer from different ethnic groups are limited. A study of the relationship between socio-demographic factors and the components of diagnostic delay (total, patient and primary care, referral and secondary care) for six cancers (breast, colorectal, lung, ovarian, prostate and non-Hodgkin's lymphoma) found that there was greater diagnostic delay for breast cancer for black and South Asian groups (Neal and Allgar, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Data on socio-economic status were not collected. The higher detection of prostate cancer in non-manual than manual social class groups is partly considered to reflect difference in use of health service (Neal and Allgar, 2005), and similar trends are likely to be seen in relatives.…”
Section: Discussionmentioning
confidence: 93%
“…It remains unclear whether the reason for the disparity by risk-group is delay in diagnosis or differing biology of cancers in the groups with less education and income compared with more advantaged groups. A recent study of UK cancer patients has shown that delay of diagnosis and treatment was longer for lower social class groups than higher social class groups and this was also apparent for breast cancer (Neal and Allgar, 2005). This delay might be a result of lower levels of knowledge regarding significant symptoms and as a result of poorer access to services.…”
Section: Discussionmentioning
confidence: 98%